Risk factors associated to the seroprevalence of brusellocis and leptospirosis in the operators of the plant benefit Pasto, Nariño - Benavides B, Bibiana; Jiménez, Efraín Alejandro; Riascos, Diego Fernando (Universidad y Salud, 2012)
The aim of this study was to identify the risk factors associated with seroprevalence of Brucellosis and Leptospirosis in operators of the slaughterhouse in Pasto, Nariño. Seropositivity for Brucella abortus was determined by the diagnostic test Rose Bengal (RB) and Leptospira sp, through diagnostic Microagglutination Test (MAT). From the 37 serum processed, 3 (8%) were positive for RB and there were no positive responses to Leptospira sp serovars evaluated with MAT test. The risk factors were identified conducting an epidemiological survey to each operator, including variables related to the transmission of the diseases in study, which were analyzed by binary logistic regression to establish the odds ratio (OR). The biological risk factors associated with brucellosis were not wearing gloves (OR = 3.11, 95% CI 1.09 – 11.52) and not using apron (OR = 2.94, 95% CI 1.12-43.04) like personal protective equipment during cattle and pigs slaughter. Therefore, it is recommended to increase control measures on the use of personal protective equipment at work in the occupational health program to minimize the risk of transmission of zoonotic diseases.